Optimization of Pretreatments for Dehydration of Bittergourd - Mudgal, V D; Pande, Vishakha K (Journal of Agricultural Engineering, 2009)
Bittergourd (Momordica charantia L) slices were i) blanched for 3 min in boiling water, ii) blanched for 3 min in 5% salt solution, and iii) dipped in 15% salt solution for 30 min. The samples dehydrated in mechanical tray dryer were found to be more acceptable as compared to sun dried and solar dried products. Exhaustive dehydration trails were conducted using mechanical tray dryer in three replications at 60, 70, 80 and 90degree C drying air temperatures. The dried bittergourd slices were packed in different types of containers for predicting their shelf life. Bittergourd slices blanched in boiling water were of the best quality followed by 5% salt solution at drying temperature of 60 and 70degree C. The samples blanched in boiling water and dehydrated at 60degree C were observed most acceptable in terms of rehydration property and nutritional quality, It also proved to be superior in colour retention up to 60 days of storage. The result showed that the rehydrated bittergourd slices could very well be utilized for substituting the fresh product during off-season.